Retrospective panoramic radiographic analysis for idiopathic osteosclerosis in Indians - Srikanth H Srivathsa (Wolters Kluwer Medknow Publications, 2016)
Introduction: Idiopathic osteosclerosis is an area of increased radiodensity observed on panoramic radiographs. The prevalence of this entity is not known, especially in Indians. Aims and Objectives: To determine the prevalence and epidemiological characteristics of idiopathic osteosclerosis. Materials and Methods: Six hundred and forty panoramic radiographs were retrospectively analyzed for the presence of idiopathic osteosclerosis by a single trained oral radiologist. Statistical Analysis: The data obtained were analyzed using Microsoft Excel (Version 2007) for Windows. Results: Idiopathic osteosclerosis was identified in 32 individuals with a prevalence of 5%. There were 21 female (65.7%) and 11 male (34.3%) participants. There were 31 single, unilateral (96.85%) osteosclerotic lesions and 1 (3.15%) bilateral lesion. Right side localization was noted in 19 participants (57.57%) and left side localization in 14 participants (42.42%). Conclusion: This study illustrates the prevalence of idiopathic osteosclerosis in Indians. Further, it depicts the characteristics of idiopathic osteosclerotic lesions.